English for tourism and catering : coursebook - Smirnova, Elizabeth; Mykhailova, Nelia; Kokhan, Olena M.; Yurchuk, Lyudmila; Vlasenko, Ludmila (My University, 2014)
This coursebook consists of two parts, which are directed to the formation of foreign language communicative competence with the students, acquirements of lexis on specialty, development of skills and abilities on reading and translating original texts on professional activity.
Keywords: діяльність ресторану; планування меню; методи приготування; готельне обслуговування; гостинність; кейтерінг бізнес; господарсько-побутова служба; оздоровчий туризм; курорт; деятельность ресторана; планирование меню; методы приготовления; гостиничное обслуживание; гостеприимство; кейтеринг бизнес; хозяйственно-бытовая служба; оздоровительный туризм; restaurant activity; menu planning; cooking methods; hotel service; hospitality; catering business; concepts; hotel-keeping; health tourism; resort; кафедра ділової іноземної мови та міжнародної комунікації; кафедра іноземних мов професійного спрямування